Efektivitas Penggunaan Media Papan Musi (Multi Fungsi) Materi KPK dan FPB pada Pembelajaran Matematika - Nurlaila, Nurlaila; Mahmudah, Istiyati (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2023)
Class IV students have difficulty understanding mathematics lessons, one of these difficulties is in the KPK and FPB material. This happens because students do not master the basics of mathematics such as addition, subtraction, multiplication and division, and students are still confused about determining the results of the KPK and FPB. Therefore, there needs to be improvements in learning. So teachers and students must play an active role in the learning process. To increase the effectiveness of students, they must use appropriate learning media, one of which is the Musi Board (Multi Function). This research uses a descriptive method with a qualitative approach and observation. The subjects of this research were teachers and students at MI Miftahul Huda II, Palangka Raya City. Based on the results of research conducted, the use of Musi Board media makes students happy and active in teaching and learning activities.